Deciphering the transfer of antimicrobial resistance genes in the urban water cycle from water source to reuse: a review - Min Chen; Gangan Wang; Baiwen Ma; Niculina Musat; Peihong Shen; Zongsu Wei; Yuansong Wei; Hans Hermann Richnow; Junya Zhang (Environment International)
Antimicrobial resistance genes (ARGs) threaten ecosystems and human health, impacting United Nations Sustainable Development Goal 3 (Good Health and Well-being). This review examines ARG occurrence and transfer within the urban water cycle (UWC) from drinking water source to wastewater reuse, highlighting molecular mechanisms and research gaps. Quantitative and metagenomic data reveal that UWC amplifies ARG spread, with plasmid-mediated ARGs rising from ∼ 2.23 % to ∼ 49.51 % and high-risk ARGs increasing from ∼ 0.25 % to ∼ 5.07 %, enhancing horizontal gene transfer in receiving waters. The primary sources of ARGs in UWC are wastewater treatment plants and combined sewage overflows. Multidrug-resistant Pseudomonas aeruginosa in drinking water treatment plant and multidrug-resistant fecal coliforms in wastewater treatment plants should be emphasized. These pose significant risks to both the environment and human health and underscore the urgent need for targeted monitoring and mitigation strategies within the UWC to safeguard public health and aquatic ecosystems. Future research should: (1) map ARG dynamics across the entire UWC, (2) identify hosts of high-risk ARGs and key pathogens, (3) elucidate HGT mechanisms and risk transmission, and (4) develop targeted control technologies for high-risk ARGs at critical UWC points. These insights will inform strategies to ensure water security and curb ARG proliferation in aquatic environments.